ACCOUNTING TREATMENT OF DEFECTIVE PRODUCTS IN DETERMINING THE COST OF PRODUCTION AT UD MEBEL SAHABAT - Hidayatullah, Hidayatullah; Norita Citra Yuliarti; Ari Sita Nastiti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the accounting treatment of defective products in determining the cost of production at UD Mebel Sahabat. Defective products produced can affect the efficiency and effectiveness of the company's operations. Method: The research employs a qualitative descriptive method with data obtained through interviews, observations, and documentation. Results: The findings reveal that defective products at UD Mebel Sahabat are caused by worker errors and low-quality raw materials. The costs incurred from defective products are recalculated to ensure the accuracy of production costs. Novelty: This study recommends improving production quality control and better accounting records to minimize losses due to defective products.